KEY FACTORS FOR DEVELOPEMENT AND ECONOMIC STABILITY IN PERU - Wong Torres, Zelma (2009)
The results of the investigation pretend to be a reference and motivational model to achieve new ways of tackling development challenges. We have analyzed the factors that are key to the sustainable economic revival of the country, because, knowing the past and present it is possible build the foundation for a better future. The university plays an important role in developing the economy of a country, mainly by research and innovations that arise out of work performed by different professionals in their area of research. That is why the universities should provide the necessary mechanisms and participate actively together with companies and government in the fields of education, accounting, economics, management, electronic engineering, industrial engineering, mathematics, computer science, among many other disciplines that exist in the universities, and to achieve specialized technical support, that is not articulated, for lack of liaison between universities, companies and State. In conclusion, we lack the correct approach to promote what we have and what we worth.